2021
DOI: 10.3390/ijms22115713
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Apple (Malus × domestica) MdERF100 in Arabidopsis Increases Resistance to Powdery Mildew

Abstract: APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) transcription factors play important roles in plant development and stress response. Although AP2/ERF genes have been extensively investigated in model plants such as Arabidopsis thaliana, little is known about their role in biotic stress response in perennial fruit tree crops such as apple (Malus × domestica). Here, we investigated the role of MdERF100 in powdery mildew resistance in apple. MdERF100 localized to the nucleus but showed no transcriptional activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Likewise, all the remaining four SNPs (SNP 1, 2, 4, and 6) were nonsynonymous mutations and resulted in substituting different amino acid residues at AA105, AA302, AA321, AA402, respectively ( Figure 3 A,B). In line with these findings, many earlier reports substantiated the roles of the AP2/ERF transcription factor family genes for mediating the pathogen responses in diverse plant species [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Likewise, all the remaining four SNPs (SNP 1, 2, 4, and 6) were nonsynonymous mutations and resulted in substituting different amino acid residues at AA105, AA302, AA321, AA402, respectively ( Figure 3 A,B). In line with these findings, many earlier reports substantiated the roles of the AP2/ERF transcription factor family genes for mediating the pathogen responses in diverse plant species [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 69%
“…The AP2/ERF group of transcription factors is the largest group of plant-specific TFs. This group is widely known for its multifarious roles, including plant development and biotic and abiotic stress regulation [ 1 , 43 , 44 ]. A recent report revealed that the C. moschata genome contains 212 AP2/ERF genes [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of MdERF11 in apple ( Malus domestica Borkh) callus cells significantly increased their resistance to B. dothidea infection, whereas silencing MdERF11 resulted in reduced resistance. MdERF11 increases plant defense against B. dothidea by stimulating the SA biosynthesis pathway [ 122 ], and MdERF100 (in Malus domestica Gala) interacts directly with MdbHLH92 to mediate resistance to powdery mildew by upregulating the JA and SA signaling pathways [ 123 ]. Overexpression of VvERF1 in grape ( Vitis vinifera Kyoho) fruits reduced the susceptibility to B. cinerea infection [ 124 ].…”
Section: Fruit Responses To Pathogen Infectionmentioning
confidence: 99%